Modal Sosial Dalam Pemberdayaan Perempuan Pada Sektor Informal Di Kelurahan Karangrejo, Kecamatan Karangrejo, Kabupaten Magetan - Harianto, Harianto (Universitas Merdeka Madiun, 2021)
Abstract— Social capital consists of three main pillars, namely trust, norms and networks. Everything will be examined through a description of the informal sector seen from women who work as traders in Karangrejo Village, Karangrejo District, Magetan Regency. The research problem that will be answered in this study is knowing social capital in empowering women in the informal sector. The purpose of this study was to determine the description of social capital in empowering women traders in Karangrejo Village. Researchers used a descriptive qualitative approach with questionnaire data collection methods and documentation. The participation of women in the informal sector in Kelurahan Karngrejo turns out to provide many functions for women’s self-development. At first they have not been able to identify the potential that exists in them, now they can recognize their own potential so that women can apply it through the skills they have mastered. Social capital efforts in women’s empowerment are expected to motivate women to be more advanced, independent and be able to develop their potential. In society so that they can be more empowered and improve their social welfare as well as help the family economy. Keywords—: social capital; women empowerment and the informal sector.